Internal Crisis Communication and Implications for Employees’ Health: A Study of Mobile Telephone Network (MTN) Nigeria $1.6 Billion Fine and Etisalat $1.2 Billion - Akisanmi, Oluwaseun Deborah (Université d'Ottawa | University of Ottawa, 2018)
Communication is the foundation of all other strategies used by companies to respond to a crisis situation. Majority of organizations pay less attention to internal crisis communication when in a crisis situation. This in turn can have negative health implications on the employees. This study surveyed how internal crisis communication takes place within an organization, its overall effects on employees, and its effect on employees’ health. The theoretical frameworks employed were Situational Crisis Communication Theory, Social Identity Theory, and Professional Identity Theory. The research survey had 90 respondents from both Etisalat and MTN. The results revealed that internal crisis communication is significant to crisis communication, as it affects employees in several aspects of their lives; such as, job security. However, contrary to previous research, the data presented does not show that internal crisis communication have negative impact on employees’ health.